An Epidemiology of Premarital Sexual Behaviour in India: Exploring Gender Differences. (September 2020) - Singh, Shri Kant; Vishwakarma, Deepanjali; Sharma, Santosh Kumar
This article analyzes the social context of increasing premarital sex in India in a gender perspective, which affects the overall contexts, patterns and the characteristics of premarital sexual behaviour. The study has been conducted on data collected from 169, 814 unmarried women and 40, 003 unmarried men, a part of the Indian Demographic Health Survey (DHS), 2015–2016. Gender differences in premarital sex were pronounced, where unmarried men were five times more likely to have premarital sex (16%) as compared to unmarried women (3%). Cox regression portrays that both men and women at younger ages were significantly more likely to initiate premarital sex. Muslim men were significantly more likely (HR = 1.16 times) to have premarital sex at younger ages. Regional variations in the prevalence of premarital sex are pronounced. Findings reveal that unmarried women with higher education, residing in urban areas and who belong to richest wealth quintile and exposed to regular mass media were more likely to have multiple sexual partners in premarital sex. There is a striking regional variation in the low prevalence of condom use in the premarital sex reported by unmarried men as well as women. In fact, unmarried men were more likely to use condom in their first as well as last premarital sexual encounter than their women counterparts. Findings suggest strengthening the empowerment of youth, especially women, through enhancing their reproductive and sexual rights education and promoting safe sexual behaviour in premarital sexual encounters.